Cyber science.rev 2 : worktext in science and technology - Ocampo, Laura V. (Manila : Rex Book Store, Inc., 2018)
"Cyber Science.rev series is a response to the challenge of revolutionizing and revitalizing the quality of Science and Technology education in the country. The lessons and learning tasks are research-based, relevant, and aimed at providing diverse learners with rich ang challenging experiences. This book addresses the basic goal of Science education : the development of a scientifically, technologically, and environmentally literate populace. Fundamental concepts and process skills to be developed are connected and integrated with the learners' technology world (interactive activities, project making, simulations, etc.) and social world (problem-solving activities, role-playing sessions, cooperative learning, etc.). These are approached following an expanding spiral progression model-building on what has already been learned more challenging content. The series is outcome-based and features varied assessment strategies that show evidences of essential understanding that are acquired and transferred. These include traditional (paper-and-pencil type) and authentic (performance and portfolio) assessment tasks coupled with rubric criteria for self-assessment."
Includes bibliographical references.
English text.